Uni-lateral Atalla Distalizing Appliance Assisted by Miniscrew Anchorage - Atalla, Ahmed (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
Introduction: A device for correcting unilateral Class II molar relationship was reported, as well as the clinical and laboratory methods for making the appliance. The clinical application for the Uni-lateral Atalla Distalizing (UAD) appliance was illustrated by a case report. The appliance's benefits and drawbacks were discussed in detail. Methods and Materials: The palatal Temporary Anchorage Device (TAD) was placed just mesial to the front molars, at their resistance centres. The appliance that is installed on the lingual sheath of the maxillary molar's band on the Class II side, extending as far anteriorly as feasible parallel to the mid-palatal raphe. The distal end of the same wire was tightened in the lingual sheath while the mesial end served as a hook into which the NiTi coil spring was inserted. Results: A Class I molar and canine associations were established in the clinical application. Overjet and overbite were likewise within acceptable limits. The roots of the teeth were fairly parallel on the post-treatment panoramic radiograph. The roots of the teeth were parallel in the post-treatment panoramic radiograph, and the supporting tissues were healthy. After treatment, the skeletal measurements on the post-treatment cephalometric radiograph indicated no significant alterations. Conclusion: Since the UAD appliance has been shown to be helpful in correcting unilateral molar Class II malocclusion, it is suggested for clinical usage in circumstances where it is indicated.